Humor com dessabor: uma análise das tiras da Mafalda no contexto escolar - Gonçalves, Jessica de Castro [UNESP] (2015)
This research turns one's eyes to the statements of some pre-school students of the Adventist College in Tupa on the comic strips of Mafalda. Given the occurrence of these in school activities, textbooks and reviews, these students presented several speeches about the strips and about the character Mafalda during the Portuguese language classes taught by the researcher of this study. Many said they did not become interested in reading these and did not understand the criticism and the effects of humor contained therein. The aim of this study is to investigate the factors involved in the act of reading this genre that carry certain disinterest and misunderstanding when in school / evaluative context. We discuss for this the conceptions of humor and gender strip submitted by students in reading activities proposed in the form of case study. It reflects also on the approach of the strip as a discursive genre in school / evaluative context, from the analysis of the teaching materials used by the studied group and the students' answers to the relations of humor and criticism present in the genre. To this end there was a case study that proposed reading activities with strips from the work Ten years with Mafalda and worked in schools, in a class of third year high school students in a college of a private school in Tupa / SP, the Adventist College. The activities were held in the Portuguese language classes, in and out of evaluative context. Here are used as theoretical apparatus of the study gender concepts / statement, act, ideology / ideological and subject sign, as designed by the Circle of Bakhtin / Medviedév / Volochínov. It is further proposed a methodology based on the chronotope of ideas, exotopy, otherness and voice discussed by the Russian circle. The categories of analysis proposals arise from the very method of conducting the case study. In strip Mafalda, seen as an ideological sign, ascertain the views of many speeches, in which ...